Boğazköy-Ḫattuša, Türkei. Die Grabung in der nördlichen Unterstadt von Ḫattuša. Die Arbeiten der Jahre 2017 und 2018 - Schachner, Andreas; Krüger, Dominique (e-Forschungsberichte des DAI, 2019)
Since 2015, the excavations in Ḫattuša have concentrated on the northern lower town. The work has investigated a district of the Hittite period whose western half is dominated by a monumental building that was used from the Old Hittite period to the older Empire period. This building overbuilt an extensive structure of the kārum period, which provides important indications of the expansion of the settlement during the early 2nd millennium BC. Beside numerous graves of the Roman imperial period, which were deepened into the Hittite buildings, a settlement of this epoch could be examined for the first time. This includes a military camp which was founded in the 1st century AD. In the 2nd century this was replaced by a complex, which probably consisted of a villa rustica and an adjoining large water basin and was used until the 4th century. The restoration work concentrated on the pottery wall, the lion basin and Yazılıkaya.